Employing Open Book Tests in Evaluating Female Graduate Students in the College of Education at Imam Mohammad bin Saud Islamic University: A Case Study - Alassaf, Ahlam Mohammed; Aliqali, Amani Ahmed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the benefits of employing open book tests in evaluating female graduate students in the College of Education at Imam Mohammad bin Saud Islamic University, by identifying the faculty members' attitudes about employing open book tests in evaluating female graduate students in the College of Education at Imam Mohammad bin Saud Islamic University. As well as, the study aimed to clarify the implications of employing open book tests in evaluating the female graduate students on the teaching practices of faculty members at the College of Education at Imam Mohammad bin Saud Islamic University. The study used the descriptive approach and relied on the interview in collecting data. The study' sample was intentionally from the faculty members of the College of Education at Imam Mohammad bin Saud University. The study' sample consisted of (two female members) in the Departments of Administration and Educational Planning, and the Foundation of Education. The study produced findings, most notably: the importance of the open book test in developing higher order thinking skills and critical and innovative thinking among female students, female students' fear of the open book test due to the inadequacy of the test requirements with the time available for it, the reluctance of some members to take open book tests due to the difficulty of planning, implementing and correcting it, their fear of female students' complaints, and their lack of confidence in the results of the test, the effectiveness of employing open book tests in evaluating female graduate students for their suitability for the advanced educational stage, the need for training in the application of open book tests in order to realize its importance and the effectiveness of its impact on female students, the importance of employing educational techniques in preparing the female students to apply the open book tests, the importance of the faculty member providing immediate feedback to the female students that supports their self-evaluation of their skills in the open book test, raising the quality of teaching the course through the evaluation of the female students at the end of each semester.
Keywords: Evaluating; Tests; Open Book; Employing